Determination of Trace Metals in Borehole, Tap, and Well Water from Dawakin Kudu Local Government Area of Kano State, Nigeria - Idris, Abdullahi Mustapha; Muhammad, Shittu Abubakar; Mathew, Twan Sale; Abubakar, Musa Yahaya; Sani, Ibrahim; Adam, Ansar Bilyaminu (Darul Yasin Al Sys, 2024)
This study investigates the concentration of trace metals in borehole, tap, and well water samples from Dawakin Kudu Local Government Area in Kano State, Nigeria. Understanding the levels of trace metals in these water sources is crucial for assessing potential health risks and ensuring safe drinking water for the local population. The samples undergo evaporation to dryness and are then pre-concentrated with 0.5 M nitric acid. The metals were analyzed using an atomic absorption spectrophotometer (AAS). The study found that all samples had iron concentrations, with the highest concentration in tap water (722.976 μg/L) and the lowest in well water (36.504 μg/L). Cadmium concentrations were highest in sample B (0.114 μg/L) and lowest in sample D (0.018 μg/L), all below WHO's permissible limit of 3 μg/L. Nickel concentrations were highest in sample C (0.336 μg/L), lowest in sample A (0.384 μg/L), and not in samples B and D (0.384 μg/L). Lead concentrations were only detected in samples A and B (0.384 μg/L), all below WHO's permissible limit of 10 μg/L. Iron was high compared to the permissible level of trace metal in water, but only in sample C, among all the samples, sample C is the safest water for drinking.